2008
DOI: 10.1038/labinvest.3700713
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-3 T78M and T78K missense mutations lead to different phenotypes in vivo and in vitro

Abstract: Caveolins are the principal protein components of caveolae, invaginations of the plasma membrane involved in cell signaling and trafficking. Caveolin-3 (Cav-3) is the muscle-specific isoform of the caveolin family and mutations in the CAV3 gene lead to a large group of neuromuscular disorders. In unrelated patients, we identified two distinct CAV3 mutations involving the same codon 78. Patient 1, affected by dilated cardiomyopathy and limb girdle muscular dystrophy (LGMD)-1C, shows an autosomal recessive mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 48 publications
0
42
0
Order By: Relevance
“…78 Only recently, Traverso et al reported a 58-year old patient affected by LGMD-1C and dilatative cardiomyopathy (p.T77M mutation). 47 It is possible that compensatory mechanisms to Cav-3 deficiency are different in cardiac and skeletal muscle tissues, but the molecular basis for this difference is not known.…”
Section: Caveolin-3 and Muscle Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…78 Only recently, Traverso et al reported a 58-year old patient affected by LGMD-1C and dilatative cardiomyopathy (p.T77M mutation). 47 It is possible that compensatory mechanisms to Cav-3 deficiency are different in cardiac and skeletal muscle tissues, but the molecular basis for this difference is not known.…”
Section: Caveolin-3 and Muscle Diseasesmentioning
confidence: 99%
“…In the patient Cav-3 protein levels are reduced by approximately 80%. Modified and reproduced by Traverso et al 47 Caveolin-3 and muscle diseasesH-CK and proven CAV3 mutations (p.G55S and p.T77M) with normal Cav-3 expression at the muscle biopsy. It is feasible that these mutants result into a stable but dysfunctional protein.…”
Section: Pathogenetic Mechanisms Of Muscle Tissue Damage In Caveolin-mentioning
confidence: 99%
See 1 more Smart Citation
“…The missense T63S mutation in the CAV3 gene resulted in decreased cell surface expression of caveolin-3 ( 228 ). Recently, another missense T78M mutation in the CAV3 gene has been identifi ed in a patient suffering from both DCM and LGMD-1C ( 229 ). Interestingly, these patients do not display skeletal muscle anomalies that are common in LGMD with underlying caveolin-3 mutations ( 228,230 ).…”
Section: Alterations In Cardiolipin Homeostasismentioning
confidence: 97%
“…Skeletal muscle contracts on demand, whereas the continuous contraction and relaxation of cardiac muscle requires more caveolin-3 to deliver a larger amount of fatty acid to mitochondria for sustained energy production ( 228 ). Moreover, caveolin-3 may be regulated by different mechanisms in skeletal and cardiac muscles ( 229 ). Because hypertrophy occurs as a secondary response to other conditions, such as valvular disease, hypertension, and ischemic heart disease ( 231, 232 ), delineation of inherited FMC and DCM changes from other noninherited conditions has become quite a challenge.…”
Section: Alterations In Cardiolipin Homeostasismentioning
confidence: 99%